(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
Many communication scholars and researchers agree that students with oral communication disabilities should be trained to be effective communicators and that effective communication strategies need to be taught to those students to improve their communication skills. They further agree that if students are not taught effective communication strategies, they will rely on the policies that do not work well, such as borrowing from language and avoidance strategies. Therefore, the author developed a way of teaching communication strategies to students with oral communication disabilities. This way is based on the concept of scaffolding, interaction hypothesis, and the social cognitive theory.